2023
DOI: 10.2174/1570159x20666220927121022
|View full text |Cite
|
Sign up to set email alerts
|

Current Naturopathy to Combat Alzheimer’s Disease

Abstract: Neurodegeneration is the progressive loss of structure or function of neurons, which may ultimately involve cell death. The most common neurodegenerative disorder in the brain happens with Alzheimer’s disease (AD) which is the most common cause of dementia. It ultimately leads to neuronal death, thereby impairing the normal functionality of the central or peripheral nervous system. The onset and prevalence of AD involve heterogeneous etiology, either in terms of genetic predisposition, neuro-metabolomic malfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 236 publications
0
1
0
Order By: Relevance
“…We observed that MS1262 treatment suppressed Tau expression that is characteristically increased in AD brains. Because neurofibrillary tangles composed of abnormally hyperphosphorylated Tau are a hallmark of AD, 61 this result demonstrated the specificity of MS1262 in targeting AD tauopathy.…”
Section: S4e and Data S1c)mentioning
confidence: 77%
“…We observed that MS1262 treatment suppressed Tau expression that is characteristically increased in AD brains. Because neurofibrillary tangles composed of abnormally hyperphosphorylated Tau are a hallmark of AD, 61 this result demonstrated the specificity of MS1262 in targeting AD tauopathy.…”
Section: S4e and Data S1c)mentioning
confidence: 77%
“…The AChE inhibitory activity of (E)-8 (17),12-labdadiene-15,16-dial or zerumin A does not appear to be reported, although zerumin A does show neuroprotective activity by preventing oxidative damage to cells [67]. Zerumin A is also reportedly a positive modulator of GABA A receptors, providing it with potential therapeutic activity against Alzheimer's disease [68]. Consequently, it is possible that one of these diterpenoids may be responsible for the AChE inhibition of A. caerulea.…”
Section: Anti-acetylcholinesterase Activitymentioning
confidence: 99%